2022
DOI: 10.1039/d1fo04375g
|View full text |Cite
|
Sign up to set email alerts
|

Elderly gastrointestinal conditions increase sterol bioaccessibility in a plant sterol-enriched beverage: adaptation of the INFOGEST method

Abstract: Elderly people suffer from a higher cardiovascular risk. Thus, the fortification of foods with plant sterols (PS), which have a cholesterol-lowering function, could be of great interest for this target...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Sterol BA is influenced by many factors, including digestion models, matrix effects, and initial sterol concentrations, so comparison across in vitro studies, especially studies using different conditions, can be difficult. However, across all studies containing both PS and Ch, the BA of Ch is consistently and substantially greater than that of PS. , Therefore, the substantial differences between PS and Ch BA are consistent with previous findings in the literature, as well as chemical differences between the molecules and different initial concentrations.…”
Section: Resultssupporting
confidence: 88%
“…Sterol BA is influenced by many factors, including digestion models, matrix effects, and initial sterol concentrations, so comparison across in vitro studies, especially studies using different conditions, can be difficult. However, across all studies containing both PS and Ch, the BA of Ch is consistently and substantially greater than that of PS. , Therefore, the substantial differences between PS and Ch BA are consistent with previous findings in the literature, as well as chemical differences between the molecules and different initial concentrations.…”
Section: Resultssupporting
confidence: 88%
“…The same modification of the gastric phase produced a significant increase (73%) in the bioaccessibility of total PS. 18 The differences between both food matrices (solid vs. liquid) could partially explain this observation. In fact, it has been observed that the GL contributes to a greater extent to the digestion of TAG in liquid foods (25%) than in solid foods (10%).…”
Section: Resultsmentioning
confidence: 99%
“…The healthy adult control conditions were performed following the INFOGEST 2.0 standardized methodology proposed by Brodkorb et al 13 with the inclusion of CE 17 to make it more physiological. Changes in the elderly conditions E1 and E2 have been selected considering a recent work by our group, 18 based on the pathophysiological changes that occur with aging and in the previous elderly adapted static in vitro digestion trials that also analyzed lipolysis and lipophilic compounds 20 since, to date, there is no standardization to apply the conditions of the elderly in simulated digestion. The simulated digestion process and the differences between the conditions of the adult and the elderly are detailed in Fig.…”
Section: Simulated Gastrointestinal Digestionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 However, the widespread use of phytosterols in the food industry was hampered by their low solubility in water and slightly soluble in oil. 9 Some recent studies investigated the bioavailability of phytosterols in food [10][11][12] and suggested that the absorption of phytosterols by humans is still unsatisfactory. Given a lower melting point, higher oil solubility, and similar physiological effects, 13 phytosterol esters are considered ideal substitutes for phytosterols.…”
Section: Introductionmentioning
confidence: 99%